ТЕХНОЛОГИК ТАЪЛИМ ЎҚИТУВЧИЛАРИНИНГ КАСБИЙ ИЖОДКОРЛИГИНИ РИВОЖЛАНТИРИШДА АКМЕОЛОГИК ЁНДАШУВНИНГ ЎРНИ - Утаева, Н.Н. (SCIENCE and SOCIETY, 2022)
This article discusses the issues of formation of professional training of teachers of technological education based on the acmeological approach, disclosure and development of their creative abilities, taking into account various aspects.